UV Spectrophotometric Method Development and Validation of Fimasartan Drug and Its Tablet Formulation - Agrawal, Kaushik S; Gandhi, Lokesh R; Bhajipale3, Nitin S. Bhajipale S (Asian Journal of Pharmaceutical Research and Development, 2019)
A novel, safe and sensitive method of Spectrophotometric estimation in UV - region has been developed for the assay of Fimasartan in its tablet formulation. The present study was undertaken to develop and validate a simple, accurate, precise, reproducible and cost effective UV spectrophotometric method for the estimation of Fimasartan bulk and pharmaceutical formulation. The method have been developed and validated for the assay of Fimasartan using Methanol as diluent. Absorption maximum (λmax) of the drug was found to be 240nm. The quantitative determination of the drug was carried out at 240nm. The method was shown linear in the mentioned concentrations having correlation coefficient R2 of 0.999. The recovery values for Fimasartan ranged from 98.74% to 99.23%.The Percent Relative Standard Deviation of interday and intraday was 0.85% and 0.75% respectively. All the parameters of the analysis were chosen according to the International Conference on Harmonisation guideline and validated statistically using Relative Standard Deviation and Percent Relative Standard Deviation. Hence, proposed method was precise, accurate and cost effective. This method could be applicable for quantitative determination of the bulk drug as well as dosage formulation. KEY WORDS: